Prospects & Models for Raising Aromatic Plants in Different Forestry Programmes for Economic Uplift - Shiva, M. P.; Jaffer, Rubab (Indian Forester, 1990)
Raising of Eucalyptus, plantations on large scale started in India about twenty years ago with greater fillip in social forestry programmes during the last decade. Therefore, trials were made to explore whether Eucalyptus citriodora or Cinnamomum camphora could be planted as an alternative species to Eucalyptus hybrid in North India and Karnataka for profitable returns, as essential oil from Eucalyptus hybrid was not found to fetch good returns. After trials, it was revealed that these two species may prove beneficial if these are planted either in block planting or along the field boundaries in forestry programmes. Some essential oil yielding grasses like Citronella, Lemon or Palmarosa may also be grown as an intercrop with these two tree species with some cultural operations. In this paper four models are suggested for adopting in social forestry programmes for increasing the productivity of fuelwood and essential oil at the same time.